Development of Eco-Sustainable Silica-Reinforced Natural Hybrid Polymer Composites for Automotive Applications. (21st December 2022) - Senthil Kumar, M.; Sakthivel, G.; Jagadeeshwaran, R.; Lakshmipathi, J.; Vanmathi, M.; Mohanraj, T.; Admassu, Yesgat
Abstract : The increasing demand for eco-friendly materials and technology has made the industry focus on bio-compatible composites. This made the researchers explore the potential of eco-friendly, bio-degradable, and inexpensive banana fibre for automotive applications. This work reports the preparation and testing of banana fibre natural hybrid composite fibres randomly oriented with and without adding silica filler (5–15 wt.%) through a hand lay-up process. The mechanical properties such as tensile modulus, flexural modulus, hardness, impact strength, and water absorption capacity were measured. Composite specimens having a fibre length of 30 mm (15 wt.% of silica) exhibited better mechanical properties. The hardness, tensile, flexural, and impact strength measured were 46.74 HV, 54.71 MPa, 127.94 MPa, and 15.19 kJ/m 2 . The results showed significant improvement in mechanical properties in silica-reinforced hybrid composite compared to composites without silica filler. The wt.% of banana fibre increases, and the number of free hydroxyls (-OH) groups increases in cellulose, increasing moisture absorption. The pattern in which the composite absorbs the moisture at room temperature is called "Fickian behaviour." Furthermore, scanning electron microscope (SEM) characterisation studied the interaction between fibre matrix and the distribution of silica reinforcement. This research concludes that bio-composites that exhibit improved mechanical properties are eco-friendly and are found to be suitable for automotive applications that meet present-day requirements.